INVESTIGATING THE EFFECT OF LOSING CUSTOMERS AND REPUTATION ON THE SUPPLY CHAIN OF BRAND MARKETING (CASE STUDY: PEGAH COMPANY PRODUCTS CONSUMERS) - Hadi Abbood, Abbas; Hadi Mahdi, Zainab; naeem Bachi, Adheem (International Journal of Supply Chain Management, 2019)
Abstract- The purpose of this research is to Investigating the Effect of losing customers and reputation on the supply chain of brand marketing (case study: Pegah products consumers). The present study is an applied research. The statistical population of this research is the customers of Pegah products. Given the unlimited size of the statistical population, the sample size is 384 people. The sampling method is also available. The validity of the questionnaires was confirmed by experts and the reliability of the questionnaires with the help of Cronbach's alpha coefficient for brand marketing of 0.878 and 0.801 for organization's reputation. To analyze the data collection using Amos software, the results show that the supply chain of brand marketing has an effect on organizational reputation. Keywords: Brand marketing, supply chain, Organizational reputation, customer, Pegah products.